2018
DOI: 10.1161/circoutcomes.118.004729
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Affordable Care Act’s Medicaid Expansion With Care Quality and Outcomes for Low-Income Patients Hospitalized With Heart Failure

Abstract: BACKGROUND: Heart failure (HF) is the leading cause of morbidity and mortality in the United States. Despite advancement in the management of HF, outcomes remain suboptimal, particularly among the uninsured. In 2014, the Affordable Care Act expanded Medicaid eligibility, and millions of low-income adults gained insurance. Little is known about Medicaid expansion’s effect on inpatient HF care. METHODS AND RESULTS: We used the American Heart Association’s Get With The Guidelines–Heart Failure registry to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
2
32
0
1
Order By: Relevance
“…By 1 January 2014, 24 U.S. states and the District of Columbia had elected to expand Medicaid eligibility requirements under the Affordable Care Act (ACA). While Medicaid expansion increased coverage of millions of previously uninsured patients and has been associated with lower cardiovascular hospitalizations (9) and mortality (10), it has not been consistently linked with greater provision of evidence-based therapies and quality of care in expansion states (11)(12)(13)(14). Understanding whether Medicaid expansion increased access to antihyperglycemic therapies for socioeconomically disadvantaged populations is critically important, given the high burden of T2DM in this population.…”
Section: Division Of Cardiology University Of Texas Southwestern Medical Center and Parklandmentioning
confidence: 99%
“…By 1 January 2014, 24 U.S. states and the District of Columbia had elected to expand Medicaid eligibility requirements under the Affordable Care Act (ACA). While Medicaid expansion increased coverage of millions of previously uninsured patients and has been associated with lower cardiovascular hospitalizations (9) and mortality (10), it has not been consistently linked with greater provision of evidence-based therapies and quality of care in expansion states (11)(12)(13)(14). Understanding whether Medicaid expansion increased access to antihyperglycemic therapies for socioeconomically disadvantaged populations is critically important, given the high burden of T2DM in this population.…”
Section: Division Of Cardiology University Of Texas Southwestern Medical Center and Parklandmentioning
confidence: 99%
“…This approach has been taken in other Medicaid expansion studies where income and poverty data were unavailable. 37 39 The SID contain a variable for median household income quartile of the patient’s ZIP code, but this was not used due to lack of precision and the potential for ecological fallacy when ZIP codes are economically heterogenous. Nonetheless, we conducted a sensitivity analysis using the lowest quartile of median household income in the ZIP code to identify low-income patients instead of using primary payer.…”
Section: Methodsmentioning
confidence: 99%
“…Existing research on the impact of the ACA Medicaid expansions on health outcomes is limited to studies that rely on self-reported health status or disease diagnosis, 6,7,[15][16][17] studies that focus on a specific population, [18][19][20][21][22] or an ecological study using aggregated data at the regional level 23 (therefore, susceptible to "ecological fallacy" 24 ). To our knowledge, there has been no national study that used individual-level clinically measured health data (e.g., blood pressure, blood glucose level, cholesterol level) to examine the relationship between the ACA's Medicaid expansions and cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%